O papel da Glia entérica e do eixo microbiota-intestinocérebro na patogênese da doença de Parkinson - Santos, Júlio César Claudino dos (2022)
Parkinson's disease (PD) is the second most common neurodegenerative disease, affecting more than 6.1 million people worldwide in 2016, characterized by the progressive loss of dopaminergic neurons in the compact part of the substantia nigra (SNpc). However, little is known about the role of the enteric glia and microbiota-gut-brain axis. We conducted the study to examine the function of the enteric glia and microbiota-gut-brain axis in a rotenone-induced rat model of Parkinson's disease. We used Wistar rats, weighing 100 to 240 g that received rotenone administration or vehicle and investigated the exploratory and motor activity, and neurodegeneration and inflammation markersin the brain and intestine segment. Behavioral analysis showed that rats receiving rotenone treatment exhibited reduced exploratory and motor activity. In the immunohistochemical analysis, we note that the animals in the rotenone group show elevated brain and intestine segment levels of IBA-1, GFAP, and S100, compared to the control group. Taken together, our data indicate that rotenone administration alters locomotor and motor activity in rats. Also, rotenone administration increases the expression in the brain and intestine of inflammatory and degeneration markers.